Analisis Willingness To Pay (WTP) Dan Kebutuhan Air Bersih Di Kota Pekanbaru - Putri, Nessa Riana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Population growth led to increased need for clean water. Provision of clean water has been managed by the water entities (PDAM). Water delivery need costs. So peoples desire to connect and pay analyzed in this study. Research on the population is divided into two categories, in the middle-upper and the lower middle class of population. The result of this research view that population wishes to subscribe, and the costs would be paid influenced by two socio-economic factors of the survey are the number of family members and revenue. The willingness to connect on a high society amounted to 62.13% and in the lower middle class is 44.44%. Tariff of willingness to pay high society is Rp 6614.96 / m3 and Rp 4971.13 / m3 for the lower middle class. This tariff are higher than average tariff of PDAM. Water supply in 2014 is 620 l / sec, it should be increased into 3946.64 l / sec for the year 2032.Keyword : willingness to pay (WTP), costs, water, Pekanbaru